FLAD1, encoding FAD synthase, is mutated in a patient with myopathy, scoliosis and cataracts. Issue 6 (14th November 2018) - García‐Villoria, Judit; De Azua, Begoña; Tort, Frederic; Mosegaard, Signe; Ugarteburu, Olatz; Texidó, Laura; Morales‐Romero, Blai; Olsen, Rikke K.J.; Ribes, Antonia
Abstract :